Perspective on Antibiotic Resistance in Bangladesh: A Critical Yet Overlooked Public Health Crisis - Md. Mahadi Hassan; Noushin Nohor (Health Science Reports)
ABSTRACT Background and Aims This article explores antibiotic resistance as a critical public health issue in Bangladesh, emphasizing its growing threat to the nation's healthcare system. As a developing country, Bangladesh faces unique challenges in managing this crisis, with antibiotic resistance posing significant risks due to its multidimensional problems to both individual health and the broader population. Methods We searched for relevant pieces of literature that discuss the antibiotic resistance problem both from a global and national perspective. Based on the importance and our objectives we selected the relevant articles. The perspective was written using the evidence and information available in those articles. Results Key factors contributing to the rise of antibiotic resistance include the irrational use and prescription of antibiotics in both healthcare settings and agriculture, incomplete doses of antibiotics, and insufficient public awareness. The article also discusses potential policy recommendations, such as the implementation of stricter antimicrobial stewardship programs, enhanced surveillance systems, and public education campaigns to reduce the misuse of antibiotics. Conclusion In conclusion, antibiotic resistance in Bangladesh requires urgent attention and coordinated efforts from all sectors of society to prevent further deterioration of public health and safeguard future generations.